SYSTEM DESIGN ON THE FRONT OFFICE HOTEL BILLING GENGGONG CIMANGGIS - Arini Saraswati; Damerianta P. Sahni, SKom, MMSI (Jurnal Sistem Informasi, 2003)
At this writing the author took the title "Draft Billing System In Front Office Hotel Genggong Cimanggis", as an enterprise which is engaged in the hospitality, the required increase in forward speed performance and reliable.Information processing stillusing manual method is not reliable. Yet in today's era of information processing problems increasingly needed because of the complexity of the problem more and more.It is expected that the existing computerized technology to be used as optimal as possible to answer the problems facing the administrative processing of billing Hotel, so as to produce the desired information.